Investigation of Wheat Germ and Oil Characteristics with Regard to Different Stabilization Techniques - Derya Arslan; M. Kürşat Demir; Ayşenur Acar; Fatma Nur Arslan (Food Technology and Biotechnology, 2020)
Research background. Utilization of wheat germ and wheat germ oil is limited due to high enzymatic activity and the presence of unsaturated fatty acids, which require stabilization techniques to overcome this problem. Experimental approach. In this study, the effects of stabilization methods (dry convective oven heating at 90 and 160 °C, microwave radiation at 180 and 360 W, and autoclave steaming) on both wheat germ and its oil were evaluated. Results and conclusions. Steaming caused the most dramatic changes in lipoxygenase activity, free fatty acid content, DPPH radical scavenging activity, and mass fractions of tocopherols and tocotrienols. Lower peroxide values were measured in the oil samples treated with convectional heating (160 °C) and steaming at temperatures above 100 °C. However, p-anisidine values of samples treated at higher temperatures were considerably greater than those of samples stabilized at lower temperatures. Oven heating at 160 °C was also one of the most effective treatments, after steaming, for the inactivation of lipoxygenase. Steaming significantly reduced mass fraction of total tocopherols, which was directly associated with the greater loss of β-tocopherol content. On the contrary, γ- and δ-tocopherol and tocotrienol homologues were abundant with higher amounts in steamed samples. α-Tocopherol and γ-tocotrienol were the most resistant isomers to stabilization processes. Novelty and scientific contribution. This study shows that the high temperature oven heating method, which is widely used in the industry for thermal stabilization of wheat germ, does not provide an advantage in oxidative stability compared to steaming and microwave applications. Steaming delayed oxidation in the germ, while further inhibiting lipoxygenase activity. Moreover, tocotrienols were more conservable. In industrial application, low-power microwave (180 instead of 360 W) and oven heating at lower temperature (90 instead of 160 °C) would be preferable.